A Review on Prevention of Diabetic Retinopathy and Ayurveda.: Array - Patwardhan, Harshada (Ayurline: International Journal of Research in Indian Medicine, 2019)
Diabetic Retinopathy (DR) is a chronic progressive, potentially sight-threatening disease of retinal microvasculature associated with prolonged hyperglycemia. The risk of development of blindness in diabetics increases by 20-25times as compared to the normal population have great concerns which lead to finding out preventive measures in Ayurveda. Currently available conventional options for diabetic retinopathy have certain limitations. Ayurveda, the traditional system of Indian subcontinent hold huge number of remedies that can be useful in the treatment of diabetes and preventing associated complications like diabetic retinopathy. Prevention is all about correcting and preventing the etiopathological mechanism (Samprapti vighatana). So as per etiopathological mechanisms described, the first and foremost care should be given to prevent madhumeha. The prevention of diabetic retinopathy revolves around treating the causes of madhumeha, management of Urdwaga Raktapitta, prevention of dhatu kshaya including oja kshaya and prevention of Agnimandya in general. Ayurvedic therapies like Pancha Karma (purification/cleansing procedures), Shamana (pacifying medicinal treatment) and Netra Kriya Kalpa, Rasayana in DR were found to be significantly effective.